Assessment of factors associated with improved glycemic control after switching from intermittently scanned to real-time continuous glucose monitoring in Japanese patients with type 1 diabetes - Eijiro Yamada; Yasuyo Nakajima; Kazuhiko Horiguchi; Shuichi Okada; Masanobu Yamada (Endocrine Journal)
The advantages of real-time continuous glucose monitoring (rtCGM) over intermittently scanned CGM (isCGM) reportedly include lower glycated hemoglobin (HbA1c) levels as well as reduced glycemic variability. However, there have been few studies of the effect of switching from isCGM to rtCGM on glycemic control, as well as the specific factors underlying any observed improvements. To that end, all patients with type 1 diabetes mellitus who used the DEXCOM rtCGM device (Terumo Corporation, Tokyo, Japan) at our institution were reviewed, and 16 individuals with type 1 diabetes who switched from isCGM to rtCGM were investigated. The patients’ HbA1c decreased in 75% of the cases (p = 0.02). On the other hand, GMI increased in 75% of the cases (p = 0.01). Intriguingly, the percentage of time below range and coefficient of variation were significantly improved with rtCGM compared to isCGM (2.9% vs. 7.6%, p = 0.016 and 35% vs. 40%, p = 0.0019, respectively). We also found that the discrepancy between HbA1c and GMI among users of isCGM was a key indicator that improved when switching to rtCGM. If discrepancies are observed between HbA1c and GMI when using isCGM, switching to rtCGM should be considered for improving glycemic control.